Devil's trill - Elias, Gerald (New York : Minotaur Books, 2009)
When a rare and valuable violin disappears after a concert, unpleasant and reclusive violin teacher Daniel Jacobus is blamed. Jacobus decides to prove his innocence by finding the violin.
Keywords: Violin teachers -- Fiction; Music -- Competitions -- Fiction; Musical fiction; Mystery fiction